Synchrotron X‐ray Tomographic Study of a Silicon Electrode Before and After Discharge and the Effect of Cavities on Particle Fracturing. Issue 7 (31st May 2016) - Zielke, Lukas; Sun, Fu; Markötter, Henning; Hilger, André; Moroni, Riko; Zengerle, Roland; Thiele, Simon; Banhart, John; Manke, Ingo
Abstract: Silicon (Si) is proposed to be one of the most promising anode materials for next‐generation lithium‐ion batteries, but unsatisfactory discharge capacity and inevitable performance deterioration prevent their commercialisation. In situ synchrotron X‐ray tomography is applied to a Si‐composite electrode‐based battery in its pristine and first discharged state and the degradation of the electron‐ and/or ion‐conducting network, as well as degradation of Si particles, is quantitatively investigated. Thus, this study is complementary to previous X‐ray tomographic studies focusing on Si particles only. On the electrode level, the Si particles located in the central part of the electrode primarily experience crack formation; on the particle level, lithiation behaviour is heterogeneous and cavities are formed during electrode preparation and battery operation. The correlation between the electrochemical activities of Si particles and their individual contact with the conducting network is investigated and quantified: Si particles will experience lithiation only under the condition that at least 40 % of their surface is electrically and ionically connected. Abstract : I'm helping ! Silicon particles larger than 150 nm fracture upon lithiation, which causes irreversible changes to the electrode, and thus, a decrease in the capacity of the battery. However, not only silicon degrades during operation, but also the electron‐conducting network changes its morphology. Cavities evolve upon lithiation, and can be quantified in terms of size and distribution, so that particles with a covered surface are of more than 60 % do not fracture (see figure).